Spatial Variability of the Hydrochemical Structure in Bottom Gravity Current in the Vema Fracture Zone - Zuev Oleg; Seliverstova Anna M. (Russian Journal of Earth Sciences)
The Vema Fracture Zone is located in the North Atlantic Ridge and extends along 11°N from 38 to 46°W. It is the main pathway for the spreading of Antarctic Bottom Water to the Northeast Atlantic. Due to its location and structure, the Vema Fracture Zone is an excellent object for studying the properties of the bottom gravity flow. An oceanographic section along the entire Vema Fracture Zone was carried out during cruise 52 of the R/V “Akademik Boris Petrov” in November–December 2022. In our work, we analyzed 25 oceanographic stations; at 15 stations, dissolved oxygen and nutrients were also determined. Such studies of the structure of the bottom gravity flow of Antarctic Bottom Water in the central channel of the Vema Fracture Zone based on high spatial resolution in situ data were made for the first time. A supercritical flow accompanied by a hydraulic jump was detected behind the main sill of the fracture zone. Simultaneous measurements of dissolved oxygen, silicate, and phosphate allowed us to examine the hydrochemical structure along the entire Vema Fracture Zone. Its analysis revealed high correlation between the distribution of hydrochemical and oceanographic parameters in both the stable flow and turbulent regimes of the current.